PERBANDINGAN NILAI DENSITAS CITRA MENGGUNAKAN GRID BERGERAK (MOVING GRID) POSISI HORISONTAL DAN VERTIKAL - Supriyati Supriyati; Wahyu Setia Budi; Heri Sutanto (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2013)
In making radiographs often differences exposure factors used when using moving of horizontal and vertical. This study aims to determine the comparative value of the density of the resulting image when using a moving grid of horizontal and vertical position. So that research results can be applied in an effort to improve the quality of the radiograph. The study begins with the initial test without the grid to determine density value, the second initial test using a moving grid both horizontally and vertically without the use of material / objects. Research continued with three aluminum thickness variation are 1 mm, 3 mm and 5 mm. Then using acrylic material three thickness variation are 1 cm, 2 cm and 3 cm. Results of image density measured using a densitometer.Results are then analyzed the data. The results of research show value of the image using horizontal grid density has smaller values than the vertical but still within the range of values density using vertical grid. Thus it can be said that the image density values using moving grid horizontal position is not different with density of the image using a vertical grid at the same exposure factors.Keywords: radiograph, moving grid, density, comparison value